Analysis of environmental protection and conservation management in the departments of the jungle region, Peru - Arias, Percy (2021)
The objective of the study was to analyze the environmental protection and conservation management developed by the environmental unit (EU) of the district municipalities of the departments of the jungle region of Peru. A descriptive, cross-sectional study was developed, and the environmental indicators reported by the National Survey of Municipalities 2019, of the National Institute of Statistics and Informatics were used. The data were organized in Microsoft Excel and analyzed using descriptive statistics with Stata version 15. The existence of a gap between the number of EU installed and those required by departments was determined, identifying a greater problem in Amazonas and Loreto. The most frequent complaints by type of contamination were: noise, water and air pollution. The main types of pollutants reported were: uncontrolled domestic animal husbandry, sewage, and deforestation and forest burning. The analysis of the coherence between the attention of complaints by type of contamination, application of management instruments and conservation actions showed the existence of EUs that worked in accordance with the legal framework (Law No. 28611), and another group of EUs that received complaints but did not apply environmental management instruments and did not carry out conservation actions. This type of environmental management was rated as deficient. The definition of an intervention strategy to deal with this situation involves monitoring the application of current laws and regulations, promoting citizen participation, and working on the most frequent types and elements of contamination.